Heat Content Anomaly and Decay of Warm‐Core Rings: the Case of the Gulf of Mexico. Issue 3 (3rd February 2020) - Meunier, Thomas; Sheinbaum, Julio; Pallàs‐Sanz, Enric; Tenreiro, Miguel; Ochoa, José; Ruiz‐Angulo, Angel; Carton, Xavier; de Marez, Charly
Abstract: In this study, we harness the 25‐year satellite‐altimeter record, in concert with a vast array of in situ measurements, to estimate the heat content anomaly of 32 warm‐core rings in the Gulf of Mexico (GoM). The decay rate of these mesoscale eddies is studied in detail, and it is shown that they release the majority of their heat as they drift in the central GoM (away from topographic obstacles). The surface heat fluxes from the eddies are shown to be small in comparison to the total rate of heat loss from the eddies, suggesting that heat is primarily released toward the surrounding water masses. Integrating the total heat evolution equation over the warm‐core rings yields an estimate of their effective lateral diffusivity coefficient. The long‐term impact of warm‐core rings on heat and salt balance in the GoM is also discussed. Key Points: The total heat content of 32 Loop Current rings is estimated using altimetry and in situ data Their decay rate is inferred and the processes driving it are discussed A range of depth‐averaged effective lateral diffusivity is proposed for Loop Current rings